Antimalarial and Immunomodulatory Activities of Tithonia diversifolia (Asteraceae) Leave Flafonoids-Rich Extract Used in Cameroonian Traditional Medecine - Ntonifor Helen Ngum; Ndoah Ellen Masakebenagha; Oumar Mahamat (Scientifica)
Background. Phytochemicals are considered the reliable source for the treatment of infection including malaria. Especially, phenols are known as potentially toxic to the growth and development of pathogens, among which flavonoids are the most extensively studied and play more intensive roles in ethnopharmacology. The immunological effect and role of T. diversifolia flavonoids-rich extract in treatment of malaria have therefore been examined in this study. Methods. In vitro test against Plasmodium falciparum and 4-day suppressive and Rane’s tests against Plasmodium berghei in mice were used to evaluate the antimalarial activities. TNF-α and INF-γ levels, phagocytic tests, and production of oxygen and nitrogen radical were assessed to appreciate the immunomodulatory activity. One-way analysis of variance followed by post hoc Student's t tests was used for data analysis. Results. T. diversifolia flavonoids-rich extract at the concentrations ranging from 0.0004 mg/ml significantly (p<0.05) inhibited in a concentration-dependent manner the growth of trophozoite up to 100% inhibition with 0.025 mg/ml at 24 and 48 hrs. Moreover, T. diversifolia flavonoids-rich extract reduced the level of parasitemia and improved in a dose-dependent manner the survival time of infected mice significantly (p<0.05) compared to their control in 4-day suppressive test as well as in Rane’s test. Additionally, T. diversifolia flavonoids-rich extract increased the TNF-α and INF-γ levels in rats infected by P. berghei. Furthermore, the flavonoid-rich extract enhanced weight of spleen in the rats, the metabolic and phagocytic activities of the peritoneal cells, and the concentration of nitric oxide and oxygen radicals in methylprednisolone-immunocompromised rats compared to the control (p<0.05). Conclusion. The study has revealed that T. diversifolia flavonoids-rich extract through its antiplasmodial and phagocytic activities is a promising treatment of malaria.